Metabolomics-Guided Isolation of Anti-trypanosomal Metabolites from the Endophytic Fungus Lasiodiplodia theobromae - Kamal, Nurkhalida; Viegelmann, Christina V.; Clements, Carol J.; Edrada-Ebel, RuAngelie (Planta Medica, 2017)
Fungal endophytes offer diverse and unique secondary metabolites, making these organisms potential sources of promising drug leads. The application of high-resolution-liquid chromatography mass spectrometry and nuclear magnetic resonance-based metabolomics to fungal endophytes is practical in terms of dereplication studies and the mining of bioactive compounds. In this paper, we report the application of metabolomics in parallel with anti-trypanosomal assays to determine the ideal conditions for the medium-scale fermentation of the endophyte Lasiodiplodia theobromae. The 1H NMR comparison between the active versus inactive fractions identified several unique chemical fingerprints belonging to the active fractions. Furthermore, by integrating high-resolution-liquid chromatography mass spectrometry data with multivariate data analysis, such as orthogonal partial least squares-discriminant analysis (OPLS-DA) and the bioactivity results of the fractions of L. theobromae, the anti-trypanosomal agents were easily discerned. With available databases such as Antibase and Dictionary of Natural Products coupled to MZmine through in-house algorithms optimized in our laboratory, the predicted metabolites were readily identified prior to isolation. Fractionation was performed on the active fractions and three known compounds were isolated, namely, cladospirone B, desmethyl-lasiodiplodin, and R-(−)-mellein. Cladospirone B and desmethyl-lasiodiplodin were among the predicted compounds generated by the OPLS-DA S-plot, and these compounds exhibited good activity against Trypanosoma brucei brucei with minimum inhibitory concentrations of 17.8 µM and 22.5 µM, respectively.
Keywords: fungal endophytes; Lasiodiplodia theobromae; Botryosphaeriaceae; anti-trypanosomal activity; HR-LCMS; NMR; metabolomics; chemometrics